Psychological distress and suicidality in psychiatric patients during the COVID-19 pandemic in Norway: A repeated cross-sectional study - Sneha Ojha; Suraj Bahadur Thapa (Elsevier, 2023)
Background: Psychiatric patients are vulnerable to disruptions caused by the Corona Virus Disease 2019 (COVID-19) pandemic. This study aimed to investigate the effects of the pandemic on mental health symptoms and suicidality among these patients during lockdowns. Methods: This repeated cross-sectional study utilized data from "Psychological distress and Coping in Patients in Community Mental Health Centers during COVID-19 pandemic (PsyCo-COVID-19) '' study, conducted in two phases between June-July 2020 and March-April 2021. It included 261 participants from six Community Mental Health Centers (CMHCs) who completed a digital questionnaire, including Norwegian version of Mini International Neuropsychiatric Interview Plus (M.I.N.I. Plus), Hopkins Symptoms Checklist (HSCL-25), Post-traumatic Stress Disorder Checklist (PCL-5). Results: A higher percentage of patients reported PTSD during the second phase of lockdown (47.4%) compared to the first phase of lockdown (33.7%). A third of participants (33.7%) reported high levels of suicidality. Moderate to severe effects of pandemic on mental health were associated with a significantly higher risk of suicide (AOR = 3.12; 95% CI: 1.50, 6.48; p = 0.0001), while having children (AOR = 0.35; 95% CI: 0.16, 0.76; p = 0.008) and being employed (AOR = 0.44; 95% CI: 0.23, 0.84; p = 0.013) were protective factors. Non-Norwegian background was associated with a higher risk of suicide (AOR = 2.59; 95% CI: 1.08, 6.19; p = 0.032). Conclusion: High prevalence of suicidality was found among patients in CMHCs in Norway, with a significant association with self-reported worsening of mental health. PTSD and suicidality increased significantly during the second phase of lockdown, emphasizing the lasting impact of the pandemic on mental health. Targeted interventions and support services are needed for psychiatric patients during times of increased stress and uncertainty. Healthcare providers should be aware of the increased risk of suicide and provide appropriate support and interventions to prevent adverse outcomes.